The Effect of Therapeutic Blockades of Dust Particles-Induced Ca2+ Signaling and Proinflammatory Cytokine IL-8 in Human Bronchial Epithelial Cells - Ju Hee Yoon; Sung Hwan Jeong; Jeong Hee Hong (Hindawi Limited, 2015)
Bronchial epithelial cells are the first barrier of defense against respiratory pathogens. Dust particles as extracellular stimuli are associated with inflammatory reactions after inhalation. It has been reported that dust particles induce intracellular Ca2+ signal, which subsequently increases cytokines production such as interleukin- (IL-) 8. However, the study of therapeutic blockades of Ca2+ signaling induced by dust particles in human bronchial epithelial cells is poorly understood. We investigated how to modulate dust particles-induced Ca2+ signaling and proinflammatory cytokine IL-8 expression. Bronchial epithelial BEAS-2B cells were exposed to PM10 dust particles and subsequent mediated intracellular Ca2+ signaling and reactive oxygen species signal. Our results show that exposure to several inhibitors of Ca2+ pathway attenuated the PM10-induced Ca2+ response and subsequent IL-8 mRNA expression. PM10-mediated Ca2+ signal and IL-8 expression were attenuated by several pharmacological blockades such as antioxidants, IP3-PLC blockers, and TRPM2 inhibitors. Our results show that blockades of PLC or TRPM2 reduced both of PM10-mediated Ca2+ signal and IL-8 expression, suggesting that treatment with these blockades should be considered for potential therapeutic trials in pulmonary epithelium for inflammation caused by environmental events such as seasonal dust storm.